Implementation of Integrated Nursing Model towards the Quality of Services and Patients’ Satisfaction - Deli . (Journal of Global Pharma Technology, 2020)
Introduction: The lack of nursing quality indirectly can be seen in patients dissatisfactory. Today society demands service that focuses on patients need, and the correct approach will be determined by the selection of the nursing model. To increase the quality of service in nursing, require a redesigned model through implementing integrated healthcare services. Methods: This is a quasi experimental study to implement an integrated nursing model using an intervention group and a control model. A total of 154 samples were chosen using consecutive sampling technique and equally distributed to each group. T-test were used to analyze the patients satisfaction level of the nursing service. Results: The result shows in the intervention group, there were 60 people (78%) that are satisfied, while in the control group, there is only four-person (5%). The increase might be caused by the nursing that is more consistent, cooperative, and responsive. The nurse understand problem identification and actively collabore in search of solution in the integrated model. Constructive integrated structure model about responsible is essential in increasing professional nurse performance. Conclusion: In conclusion, there are significant differences; higher patient satisfaction level on the model implementing integrated model than without implementing integrated model.Keywords: Integrated model, Service Focus on Patients.